Tuning Rheological Performance of Silica Concentrated Shear Thickening Fluid by Using Graphene Oxide. (23rd March 2015) - Huang, Wenchao; Wu, Yanzhe; Qiu, Ling; Dong, Cunku; Ding, Jie; Li, Dan
Abstract : The addition of a small amount of graphene oxide into a traditional colloidal silica-based shear thickening fluid (STF) can lead to a significant change in viscosity, critical shear rate, storage modulus, and loss modulus of STF. This finding provides an effective way to prepare stronger and light-weight STFs.